2023
DOI: 10.3390/nu15061362
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of Vitamin D on Non-Alcoholic Fatty Liver Disease (NAFLD) Progression in the Zebrafish Model

Abstract: A major cause of chronic liver disease, cirrhosis, and hepatocellular carcinoma, non-alcoholic fatty liver disease (NAFLD) results from excessive liver fat accumulation. Vitamin D (VitD) plays multiple important roles in diverse physiologic processes. Here, we describe the role of VitD in the complex pathogenesis of NAFLD and explore the possible therapeutic role of VitD supplementation in NAFLD therapy. To compare the effect of VitD to other interventions such as low-calorie diet, we induced NAFLD in young ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Aside from its impact on calcium–phosphorus metabolism and bone mineralization, Grinberg L. lists its anti-inflammatory, immune-system-regulating, fibrosis-inhibiting, and lipid-metabolism-regulating actions. Additionally, studies on animal models have demonstrated its ability to limit fat accumulation in the liver, which is noteworthy in preventing further consequences of the disease [ 49 ]. There are also reports of its anti-cancer properties [ 50 ].…”
Section: Vitamins and Trace Elements As Supportive Elements In The Pr...mentioning
confidence: 99%
“…Aside from its impact on calcium–phosphorus metabolism and bone mineralization, Grinberg L. lists its anti-inflammatory, immune-system-regulating, fibrosis-inhibiting, and lipid-metabolism-regulating actions. Additionally, studies on animal models have demonstrated its ability to limit fat accumulation in the liver, which is noteworthy in preventing further consequences of the disease [ 49 ]. There are also reports of its anti-cancer properties [ 50 ].…”
Section: Vitamins and Trace Elements As Supportive Elements In The Pr...mentioning
confidence: 99%
“…The accumulation of lipid metabolites is closely associated with obesity or obesityrelated NAFLD [19]. NAFLD is often associated with metabolic syndrome features, such as dyslipidemia, hypertension, and T2DM [20]. The intrahepatic triglyceride accumulation (i.e., steatosis, the hallmark feature of NAFLD) results from an imbalance between complex molecular pathways of lipid metabolism [20].…”
Section: Introductionmentioning
confidence: 99%
“…NAFLD is often associated with metabolic syndrome features, such as dyslipidemia, hypertension, and T2DM [20]. The intrahepatic triglyceride accumulation (i.e., steatosis, the hallmark feature of NAFLD) results from an imbalance between complex molecular pathways of lipid metabolism [20]. Animal models are critical tools for studying NAFLD, as well as the development of therapeutic drugs and prevention and treatment strategies [20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations